2008
DOI: 10.1002/ca.20739
|View full text |Cite
|
Sign up to set email alerts
|

The marginal mandibular branch of the facial nerve in Koreans

Abstract: The marginal mandibular branch (MMB) has a particular risk of injury during surgical procedures in the submandibular region, especially over the lower border of the mandible. The facial nerve has been described in many studies, but the MMB is dealt with generally as a branch of the facial nerve. The purpose of this study was to document the anatomy of the MMB by correlation with anatomical landmarks. Eighty-five facial halves were examined for this study. The MMB was classified according to the number of branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 14 publications
3
40
0
2
Order By: Relevance
“…Several researchers described the course of the marginal mandibular branch of the facial nerve in relationship to the lower edge of the mandible (Basar et al, 1997;Kim et al, 2009;Potgieter et al, 2005). Facial vessels show the close contact with the marginal mandibular branch at the mandibular crossing point.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers described the course of the marginal mandibular branch of the facial nerve in relationship to the lower edge of the mandible (Basar et al, 1997;Kim et al, 2009;Potgieter et al, 2005). Facial vessels show the close contact with the marginal mandibular branch at the mandibular crossing point.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the nerve was found medial to the vein in 17% of the cases, from which in 6% it divided after crossing the vein and in 11% before. No significant difference was found according to gender [11]. Additionally, Dingman and Grabb [6] noticed that the RV was located on the medial side of the mandibular branch of the FN in 98% (98/100) and lateral in 2% (2/100) of the specimens.…”
Section: Discussionmentioning
confidence: 93%
“…The authors also noticed that in 74% of the cases, the vein crossed the nerve at a level between the bifurcation and ramification points [12]. After examining 85 facial halves in cadavers, Kim et al [11] observed lateral position of the FN cervicofacial division in relation to the vein in 83%. From these cases, in 52% the nerve was divided into its branches after crossing the vein, whilst in 31% the division occurred before the crossing point level.…”
Section: Discussionmentioning
confidence: 96%
“…From these branches; 1 of them was buccal, 3 of them were marginal mandibular and 1 of them was cervical. Kim et al [8] and Lineweaver et al [9] have reported a high percentage of 2 and 3 branched marginal mandibular nerves. In the study of Farahvash et al [6], a single marginal mandibular branch was seen in 95.7% of the cadavers.…”
Section: Discussionmentioning
confidence: 97%